2005
DOI: 10.1037/0894-4105.19.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Linear Modeling of California Verbal Learning Test--Children's Version Learning Curve Characteristics Following Childhood Traumatic Head Injury.

Abstract: California Verbal Learning Test-Children's Version (CVLT-C) indices have been shown to be sensitive to the neurocognitive effects of traumatic brain injury (TBI). The effects of TBI on the learning process were examined with a growth curve analysis of CVLT-C raw scores across the 5 learning trials. The sample with history of TBI comprised 86 children, ages 6-16 years, at a mean of 10.0 (SD=19.5) months postinjury; 37.2% had severe injury, 27.9% moderate, and 34.9% mild. The best-fit model for verbal learning w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…In the CVLT manual, the rate of learning across the five trials is calculated as the slope of a simple linear function (Delis et al, 1987). However, and in accordance with previous studies (Warschausky, Kay, Chi, & Donders, 2005), we found that our data were best fitted by a quadratic model Y = A + Bx + Cx 2 (r 2 > .98 for the 3 learning curves of controls, MCI and AD subjects, Figure 1). In this equation, the coefficient B represents the rate of acquisition and the coefficient C the rate of deceleration of learning (Warschausky et al, 2005).…”
Section: Learningsupporting
confidence: 69%
See 1 more Smart Citation
“…In the CVLT manual, the rate of learning across the five trials is calculated as the slope of a simple linear function (Delis et al, 1987). However, and in accordance with previous studies (Warschausky, Kay, Chi, & Donders, 2005), we found that our data were best fitted by a quadratic model Y = A + Bx + Cx 2 (r 2 > .98 for the 3 learning curves of controls, MCI and AD subjects, Figure 1). In this equation, the coefficient B represents the rate of acquisition and the coefficient C the rate of deceleration of learning (Warschausky et al, 2005).…”
Section: Learningsupporting
confidence: 69%
“…However, and in accordance with previous studies (Warschausky, Kay, Chi, & Donders, 2005), we found that our data were best fitted by a quadratic model Y = A + Bx + Cx 2 (r 2 > .98 for the 3 learning curves of controls, MCI and AD subjects, Figure 1). In this equation, the coefficient B represents the rate of acquisition and the coefficient C the rate of deceleration of learning (Warschausky et al, 2005). The intercept component was not considered in the analysis as it represents the number of words recalled in an nonexistent trial zero.…”
Section: Learningsupporting
confidence: 64%
“…Possible predictors of memory outcome have also been investigated and include age at injury (Farmer et al, 1999;Yeates et al, 1995), suggesting that younger age at injury results in poorer outcome; severity (Catroppa & Anderson, 2003;Warschausky, Kay, Chi, & Donders, 2005), where those with mild-moderate injuries are often found to perform similarly to control children, while those with severe TBI more poorly; premorbid learning problems (Farmer et al, 2002;Haas, Cope, & Hall (1987) and family functioning (Rivara et al, 1993), with stronger preinjury child and family functioning resulting in better outcomes.…”
Section: Introductionmentioning
confidence: 98%
“…Several recent studies have attempted to model short-term learning in a multiple-trial word recall task using contemporary growth curve modeling techniques (e.g., Jones et al, 2005;Poreh, 2005;Nettelbeck, Rabbitt, Wilson, & Batt, 1996;Royall, Palmer, Chiodo, & Polk, 2003;Royall, Palmer, Chiodo, & Polk, 2005;Warschausky, Kay, Chi, & Donders, 2005). Among the results of these studies were significant relations between the learning parameters in these models and age, race/ethnicity, speed of processing, verbal knowledge, and global cognitive ability level.…”
mentioning
confidence: 96%